Breaking the Spell: The Representation of Trauma in Disney-Animated Films - Ho, Katrina (Tufts Archival Research Center, 2022)
A study on the presentation of trauma in children's media -- specifically post 2010s Disney feature-length animated films.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Eliot-Pearson Dept. of Child Study and Human Development.; Advisor: Julie Dobrow.; Committee: Julie Dobrow and Kerri Modry-Mandell.